E-mental health implementation in inpatient care: Exploring its potential and future challenges - Van Assche, Eva; Bonroy, Bert; Mertens, Marc; Van den Broeck, Lore; Desie, Kimberly; Bolinski, Felix; Amarti, Khadicha; Kleiboer, Annet; Riper, Heleen; Van Daele, Tom (Frontiers in Digital Health, 2022)
Background: There is a great evidence base today for the effectiveness of e-mental health, or the use of technology in mental healthcare. However, large-scale implementation in mental healthcare organisations is lacking, especially in inpatient specialized mental healthcare settings. Aim: The current study aimed to gain insights into the factors that promote or hinder the implementation of e-mental health applications on organisational, professional and patient levels in Belgium. Methods: Psychiatric hospitals and psychiatric departments of general hospitals and their professionals and patients were invited to use Moodbuster, which is a modular web-based platform with a connected smartphone application for monitoring. They completed pre- and post-implementation questionnaires on themes such as perspectives toward technological applications in mental healthcare, reasons to participate or to decline participation, and experiences with the Moodbuster platform. Results: Main reasons for the organisations to participate in the implementation study were a general interest in e-mental health and seeing it is a helpful add-on to regular treatment. The actual use of Moodbuster by professionals and patients proved to be challenging. Implementation was hindered by technical difficulties and inpatient care specific factors such as lack of structural facilities to use e-mental health and patient-specific factors. Professionals saw value in using e-mental health applications for bridging the transition from inpatient to outpatient care. Conclusions: The current implementation study reveals several important barriers to overcome in order to successfully implement e-mental health in inpatient psychiatric care.